Influence a Healthy Lifestyle of the Youth on the Russian Economy - Zazulina, Evgeniya V.; Berezhnaya, Elena S.; Berezhnaya, Aleksandra V.; Zheltushkina, Elena V.; Koloskova, Natalia V.; Strichko, Anna V. (International Journal of Economics and Financial Issues, 2016)
One of the main and most important components of a country’s wealth is the health of the citizens. Established fact that in the process of protecting and promoting the health of the population consumes a significant portion of gross domestic product, and as such health is a special economic resource, which largely determines the high efficiency of socio-economic development of the country and its regions. Today, more and more researchers in Economics have come to believe that the commitment of the population to a healthy lifestyle, avoiding harmful habits, leads to a positive effect of the growth of the national economy. Based on the results of these studies, it was found that in our modern time, the health becomes a social property of a successful person that ensures the person in the conditions of market economy competitiveness, security in the financial sector, professional longevity and a comfortable old age. We conclude that health in modern society takes on a special priority, and becomes an important issue for theoretical research and practical testing. Keywords: healthy lifestyle, health, gross domestic product, economic development, market economy JEL Classifications: O12, O15, O44, O47